miRNA Combinatorics and its Role in Cell State Control—A Probabilistic Approach - Mahlab-Aviv, Shelly; Linial, Nathan; Linial, Michal (Frontiers in Molecular Biosciences, 2021)
A hallmark of cancer evolution is that the tumor may change its cell identity and improve its survival and fitness. Drastic changes in microRNA (miRNA) composition and quantities accompany such dynamic processes. Cancer samples are composed of a mixture of cells that are at varying stages of cancerous progress. Therefore, molecular profiling from cancer biopsy represents the sample averaging with minimal insight on cell identity. In this study, we consider the degree to which altering miRNAs composition shifts cell behavior. We used COMICS, an iterative framework that simulates the stochastic events of miRNA-mRNA pairing, using a probabilistic approach. COMICS simulates the likelihood that cells change their transcriptome following 100k iterations. Results of COMICS from the human cell line (HeLa) confirmed that most genes are resistant to miRNA regulation. However, COMICS results suggest that the composition of abundant miRNAs dictates the nature of cells at their steady state. In silico perturbations of cell lines (i.e., by overexpressing miRNAs) allowed classifying genes according to their sensitivity and resilience to any combination of miRNA perturbations. Our results expose an overlooked quantitative dimension for sets of genes and their regulation by miRNAs in living cells. The immediate implication is that even relatively modest overexpression of specific miRNAs may shift cell identity and impact cancer evolution.